Factors influencing dementia preventive behaviors among older people in Chaiyaphum Province - Khunkhavan, Torranin; Hoyrat, Pankarin; Tuanwisetkul, Suwaree (Thai Journal of Nursing, 2023)
The objectives of this predictive correlational research were to study dementia preventative behaviors and to find factors influencing dementia preventive behaviors among older people in Chaiyaphum Province. A sample of 275 older people was recruited by purposive sampling. The research instruments consisted of questionnaires to elicit 1) demographic data, 2) knowledge of dementia, 3) perceived self-efficacy in dementia prevention, 4) social support and 5) dementia preventive behaviors. The content validity index were between 0.67-1.00. Reliability coefficients were 0.86, 0.83, 0.78 and 0.75 respectively. Descriptive statistics, and multiple regression analysis were used in data analysis. Results are as follows. 1) The overall dementia preventive behaviors of older people are at moderate level (M = 2.15, SD = 0.34). 2) Factors influencing dementia preventive behaviors of older people are perceived self-efficacy in dementia prevention (Beta = 0.334), social support (Beta = 0.224) and knowledge of dementia (Beta = 0.161) at p < .05. These factors accounted for 28.7 percent of the variance in dementia preventive behaviors.